2000
DOI: 10.1099/00207713-50-5-1829
|View full text |Cite
|
Sign up to set email alerts
|

Symbiobacterium thermophilum gen. nov., sp. nov., a symbiotic thermophile that depends on co-culture with a Bacillus strain for growth.

Abstract: NOTESymbiobacterium thermophilum gen. nov., sp. nov., a symbiotic thermophile that depends on co-culture with a Bacillus strain for growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 12 publications
3
56
0
Order By: Relevance
“…For the details of the taxonomical characteristics of S. thermophilum, see previous reports. 5,13) The circular chromosome of S. thermophilum consisted of 3.67 Mb DNA with 68.7% G+C. Despite this high G+C content, we found that the genome of S. thermophilum showed overall similarity to that of Firmicutes.…”
Section: Complete Genome Sequencingmentioning
confidence: 63%
See 1 more Smart Citation
“…For the details of the taxonomical characteristics of S. thermophilum, see previous reports. 5,13) The circular chromosome of S. thermophilum consisted of 3.67 Mb DNA with 68.7% G+C. Despite this high G+C content, we found that the genome of S. thermophilum showed overall similarity to that of Firmicutes.…”
Section: Complete Genome Sequencingmentioning
confidence: 63%
“…2). 5) Furthermore, it represented a novel deep branch between the clades for high-G+C and low-G+C bacteria. Based on the result of 16S rRNA genebased phylogeny and its high-G+C content (68.7%), S. thermophilum was classified into Actinobacteria (high G+C Gram-positive bacteria)(for example, see NCBI Taxonomy Homepage, http://www.ncbi.nlm.nih.…”
Section: Taxonomic Characteristicsmentioning
confidence: 99%
“…However, neither a moderately thermophilic nor a mesophilic cenancestor can be excluded for this root, since two recently discovered thermophilic Clostridia occupy a position near the root in concatenated protein sequence trees (Wu et al 2005). Symbiobacterium thermophilum (Ohno et al 2000) grows optimally at 608C, and Carboxydothemus hydrogenoformans (Wu et al 2005) grows optimally at 788C. Thus this new root parsimoniously places constraints on the growth temperature of the cenancestor.…”
Section: Discussionmentioning
confidence: 99%
“…However, since GTs are less likely to occur between phylogenetically and functionally distant groups ( Jain et al 1999;Jain 2003), their effects may be reduced by choosing taxonomic groups that are phylogenetically well separated, thereby minimizing intergroup gene/indel transfers. These phylogenetically well-separated and relatively homogeneous prokaryotic taxa (Skophammer et al 2006Lake et al 2007) are: the archaebacteria, the Bacilli and relatives, the Clostridia and relatives, the Actinobacteria and the double-membrane, Gramnegative, prokaryotes (Cyanobacteria, Proteobacteria, Spirochaetes, Chlorobi, Chloroflexi and 17 additional phyla) (for more detailed definitions of these groups, including some recent taxonomic changes, see Ohno et al (2000), Garrity & Holt (2001), Wu et al (2005) and Lake et al (2008)). Together these five prokaryotic super-taxa, plus the eukaryotes, include all-known life (Boone & Castenholz 2001).…”
Section: The Diversity Of Life On Earthmentioning
confidence: 99%
“…A producer of heatstable tryptophanase and b-tyrosinase, Symbiobacterium thermophilum, grows only in mixed cultures with Bacillus strains, Escherichia coli, or Thermus thermophilus possibly being supplied with some ubiquitous metabolite(s). 13,14) Microbial degradation of polyvinyl alcohol (PVA) is achieved only in mixed cultures. A PVA-oxidizing bacterium, a Pseudomonas strain, requires pyrroloquinoline quinone (PQQ); the partner bacterium, also a Pseudomonas strain, supplies PQQ and uses oxidized PVA.…”
mentioning
confidence: 99%